Maternal-fetal attachment protects against postpartum anxiety: the mediating role of postpartum bonding and partnership satisfaction - Matthies, Lina; Marshall, Anne; Sohn, Christof; Wallwiener, Markus; Wallwiener, Stephanie (Archives of gynecology and obstetrics, 2020)
Maternal mental disorders develop frequently during the perinatal period, and can have detrimental effects on the developing bond between a mother and her child. While depression has already been widely associated with bonding disorders, the link between anxiety disorders and maternal-fetal attachment has received only limited attention. This study aimed to explore the link between maternal-fetal attachment in the third trimester and postpartum anxiety, as previous research has suggested a potentially protective association. Additionally, we hypothesized a mediating influence of postpartum bonding and partnership satisfaction as additional measurements of attachment capacity. Self-report questionnaires assessing maternal-fetal attachment, postpartum bonding, anxiety, depression, and partnership quality were completed at three time points: third trimester (T1, N = 324), first week postpartum (T2, N = 249), and 4 months postpartum (T3, N = 166). Conditional process analyses were used to test for mediation. A statistically significant negative correlation of maternal-fetal attachment was found with maternal anxiety postpartum. Overall, the analyses supported the mediation hypothesis. There was a significant, indirect effect of maternal-fetal attachment during pregnancy on state anxiety in the first week postpartum, mediated through postpartum bonding quality and partnership satisfaction. All three variables together accounted for 18.25% (state anxiety) or 30.35% (trait anxiety) of the variance in postpartum anxiety. Our results showed that a close maternal-fetal attachment buffers postpartum symptoms of anxiety, partially mediated through postpartum bonding and partnership satisfaction. Therefore, strengthening the maternal-fetal attachment and the partnership during pregnancy has the potential to reduce maternal postpartum symptoms of anxiety.